2017
DOI: 10.1158/0008-5472.can-16-2717
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Subtypes and Gene Expression Profiles in Primary and Metastatic Breast Cancer

Abstract: Biological changes that occur during metastatic progression of breast cancer are still incompletely characterized. In this study, we compared intrinsic molecular subtypes and gene expression in 123 paired primary and metastatic tissues from breast cancer patients. Intrinsic subtype was identified using a PAM50 classifier and χ2 tests determined the differences in variable distribution. The rate of subtype conversion was 0% in basal-like tumors, 23.1% in HER2-enriched (HER2-E) tumors, 30.0% in luminal B tumors,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
186
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(217 citation statements)
references
References 50 publications
16
186
0
4
Order By: Relevance
“…Subtle Her2 and LumB profile shifts were also the most common when observing continuous PAM50 probability scores, even in samples that remained concordant in their discrete PAM50 assignments. A recent targeted expression study analyzed PAM50 assignments in 123 matched breast cancer metastases, and the authors found similar frequencies of LumB and Her2 acquisitions in ER-positive metastatic tumors (30). Given this transcriptional evolution to more LumB and Her2 profiles, a thoughtful reevaluation of therapy selection in the advanced and perhaps the adjuvant setting may be necessary -especially considering HER2-targeted therapies are generally reserved for patients with HER2-positive primary disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subtle Her2 and LumB profile shifts were also the most common when observing continuous PAM50 probability scores, even in samples that remained concordant in their discrete PAM50 assignments. A recent targeted expression study analyzed PAM50 assignments in 123 matched breast cancer metastases, and the authors found similar frequencies of LumB and Her2 acquisitions in ER-positive metastatic tumors (30). Given this transcriptional evolution to more LumB and Her2 profiles, a thoughtful reevaluation of therapy selection in the advanced and perhaps the adjuvant setting may be necessary -especially considering HER2-targeted therapies are generally reserved for patients with HER2-positive primary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the observed LumB enrichments, our data suggest breast cancer cells may develop a more proliferative phenotype following bone colonization, and the strong enrichment of E2F signature in metastatic disease again highlights the CDK/Rb/E2F pathway as a prime target. Interestingly, another study that utilized a targeted gene expression platform found proliferative gene signatures in ER-positive metastases may be more accurate at predicting overall survival than signatures in the primary tumor (30). A survival analysis for this work was impractical given the small set of patient-matched pairs, but future meta-analyses are warranted to determine if gene expression signatures in metastases are better predictors of overall survival in the advanced setting, especially given the significant transcriptomic shifts observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have described HER2 amplification as a known mechanism of resistance to endocrine therapy (39). Furthermore, preliminary evidence has shown that ER + tumors that metastasize often have features of HER2 enrichment in them (40). This molecular diversity of ER + tumors (16,41) may explain the differential response of many patients' metastases to AI therapy.…”
Section: Shared Transcriptional Program In Metastasesmentioning
confidence: 94%
“…In this particular study, molecular changes in Her2 and intrinsic subtype switching to Her2-enriched subtypes can be associated with brain metastasis, indicating that the brain micro-environment may favor the progression of Her2 driven malignancies. In a separate study, PAM50 subtype classification of 123 paired primary and metastatic breast tumors revealed that subtype switching does indeed occur predominantly in cases where the primary tumors were classified as luminal A, luminal B or Her2-enriched [40], albeit these subtype switches could be driven by other mechanisms such as clonal evolution rather than plasticity. Notwithstanding that, evidence for a hierarchical model in breast cancer metastases has been reported [41].…”
Section: Plasticity Of Breast Cancer Subtypesmentioning
confidence: 99%